Solution chemistry and phase solubility diagrams of CL-20/MTNP energetic cocrystals. Issue 12 (4th March 2020) - Tang, Luyang; Li, Hongzhen; Tan, Yanwei; Liu, Tiansheng; Yang, Zongwei
Abstract : The solubility behavior and solution chemistry of CL-20/MTNP (2, 4, 6, 8, 10, 12-hexanitro-hexaaza-isowurtzitane/1-methyl-3, 4, 5-trinitropyrazole) energetic cocrystals in organic solvents were first investigated to offer some important information on thermodynamics. Abstract : The solubility behavior and solution chemistry of CL-20/MTNP (2, 4, 6, 8, 10, 12-hexanitro-hexaaza-isowurtzitane/1-methyl-3, 4, 5-trinitropyrazole) energetic cocrystals in organic solvents were first investigated to offer some important information on thermodynamics. The phase solubility diagram (PSD) and eutectic point ( K eu1 ) of three solvents were also determined. Moreover, the solubility behavior of CL-20/MTNP energetic cocrystals was explained using the solubility product and solution complexation theories. The solution complexation results indicated that the CL-20/MTNP cocrystal has the strongest complexation effect in ethanol. The K eu1 values were all below 1 in three studied solvents, suggesting that the CL-20/MTNP cocrystal was less soluble than the other two pure components. Furthermore, studying the solubility behavior and solution chemistry of the CL-20/MTNP cocrystals has provided further insights into the screening, preparation and scaling-up of energetic cocrystals.